2010
DOI: 10.1177/1359786810382057
|View full text |Cite
|
Sign up to set email alerts
|

Review: Mortality trends in the general population: the importance of cardiorespiratory fitness

Abstract: Cardiorespiratory fitness (CRF) is not only an objective measure of habitual physical activity, but also a useful diagnostic and prognostic health indicator for patients in clinical settings. Although compelling evidence has shown that CRF is a strong and independent predictor of all-cause and cardiovascular disease mortality, the importance of CRF is often overlooked from a clinical perspective compared with other risk factors such as hypertension, diabetes, smoking, or obesity. Several prospective studies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
403
2
33

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 526 publications
(449 citation statements)
references
References 92 publications
(108 reference statements)
11
403
2
33
Order By: Relevance
“…This is more than double the level of sedentary behavior reported in older populations (>60 years) (mean=5.3h per day) (Harvey et al, 2014) and similar to the levels found in people with psychosis (Stubbs et al, 2016). The extent to which sedentary behavior in people with bipolar disorder contributes to the previously observed physical fitness impairments (Vancampfort et al, 2015c; and metabolic abnormalities (Vancampfort et al, 2015d), both predictors for cardiovascular diseases and premature mortality (Lee et al, 2010), is unknown. Given that sedentary behavior is modifiable, understanding sedentary behavior levels and correlates might offer a unique opportunity to reduce the considerable cardio-metabolic rates seen in people with bipolar disorder Vancampfort et al, 2013).…”
Section: Introductionsupporting
confidence: 49%
“…This is more than double the level of sedentary behavior reported in older populations (>60 years) (mean=5.3h per day) (Harvey et al, 2014) and similar to the levels found in people with psychosis (Stubbs et al, 2016). The extent to which sedentary behavior in people with bipolar disorder contributes to the previously observed physical fitness impairments (Vancampfort et al, 2015c; and metabolic abnormalities (Vancampfort et al, 2015d), both predictors for cardiovascular diseases and premature mortality (Lee et al, 2010), is unknown. Given that sedentary behavior is modifiable, understanding sedentary behavior levels and correlates might offer a unique opportunity to reduce the considerable cardio-metabolic rates seen in people with bipolar disorder Vancampfort et al, 2013).…”
Section: Introductionsupporting
confidence: 49%
“…3,4 Low fitness is a better predictor of mortality than are obesity 5 or hypertension, 3,6 which are health risk factors afforded far greater emphasis than fitness by the media and by most health professionals.…”
Section: Sport and Exercise Versus Physical Activitymentioning
confidence: 99%
“…Health-related physical fitness is determined by aerobic capacity, body composition and musculoskeletal profile ( flexibility, muscular strength and endurance). Aerobic capacity (as measured by the maximal oxygen uptake, reflects the functionality of respiratory, cardiovascular and muscular systems and varies amongst individuals due to genetic factors, age, sex, habitual daily levels of physical activity and health status 47 .…”
Section: Physical Fitness In Nfmentioning
confidence: 99%
“…Aerobic capacity (as measured by the maximal oxygen uptake, reflects the functionality of respiratory, cardiovascular and muscular systems and varies amongst individuals due to genetic factors, age, sex, habitual daily levels of physical activity and health status 47 .…”
mentioning
confidence: 99%